Diagnosis of uterine lymphoma on cervical pap smear: Case report and review of literature - Preethi Dileep Menon; Hamza Tariq; Cynthia Forker; Alia Nazarullah (Elsevier, 2021)
Hematolymphoid neoplasms rarely involve the cervix, with an overall incidence of less than 1% among all cervical malignancies. Clinical presentations include abnormal uterine bleeding, pelvic discomfort, dyspareunia, back pain and vaginal discharge. Cervical Papanicolaou Smear is an important screening tool for early detection of cervical epithelial lesions; however, a high index of suspicion is needed to recognize non-epithelial malignancies like lymphoma. We report the case of a 48-year-old woman who presented with abnormal vaginal bleeding. Pap smear showed large atypical discohesive cells with vesicular chromatin and prominent nucleoli. A cell block preparation with immunohistochemistry confirmed large B-cell lymphoma. This diagnosis is important due to management strategy differences of chemoradiation over surgery in hematologic malignancies. A review of literature of hematologic malignancies diagnosed on Pap smear is also reported.